1991
DOI: 10.1083/jcb.112.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of constitutive secretion using semi-intact cells: regulation by GTP but not calcium.

Abstract: Abstract. Regulated exocytosis in many permeabilized cells can be triggered by calcium and nonhydrolyzable GTP analogues. Here we examine the role of these effectors in exocytosis of constitutive vesicles using a system that reconstitutes transport between the transGolgi region and the plasma membrane. Transport is assayed by two independent methods: the movement of a transmembrane glycoprotein (vesicular stomatitis virus glycoprotein [VSV G protein]) to the cell surface; and the release of a soluble marker, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
94
1

Year Published

1991
1991
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 55 publications
11
94
1
Order By: Relevance
“…Synaptophysin is sulfated on carbohydrate residues Sulfation of proteins on tyrosine and carbohydrate residues, both of which occur selectively in the TGN (Kimura et al, 1984;Baeuerle and Huttner, 1987), has been found to be a powerful tool to study protein exit from the TGN (Tooze and Huttner, 1990;Miller and Moore, 1991 (Wiedenmann and Franke, 1985) from PC12 cells after a 5 min pulse with methionine followed by a 2 h chase ( Figure 1, (Figure 2A,B,G; see also Tooze and Huttner, 1900 . , .…”
Section: Resultsmentioning
confidence: 99%
“…Synaptophysin is sulfated on carbohydrate residues Sulfation of proteins on tyrosine and carbohydrate residues, both of which occur selectively in the TGN (Kimura et al, 1984;Baeuerle and Huttner, 1987), has been found to be a powerful tool to study protein exit from the TGN (Tooze and Huttner, 1990;Miller and Moore, 1991 (Wiedenmann and Franke, 1985) from PC12 cells after a 5 min pulse with methionine followed by a 2 h chase ( Figure 1, (Figure 2A,B,G; see also Tooze and Huttner, 1900 . , .…”
Section: Resultsmentioning
confidence: 99%
“…Release of preformed products from the regulated pathway is further distinguished by being dependent upon protein synthesis, whereas the constitutive pathway is not [43]. The generation of both constitutive vesicles and secretory granules of the regulated pathway is, however, GTP-dependent [44][45][46].…”
Section: Protein Secretory Pathways: a General Outline Leader And Leamentioning
confidence: 99%
“…The method of Miller and Moore (1991) for permeabilizing cells with SLO was Vol. 6, February 1995 modified slightly and used to allow BFA direct access to the cytosol of wild-type or mutant CHO cells.…”
Section: Additional Assays For Bfa-resistant Mutantsmentioning
confidence: 99%